2022
DOI: 10.1093/cvr/cvac087
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers for management of cancer therapeutics-related cardiac dysfunction

Abstract: Cancer therapeutics related cardiac dysfunction (CTRCD) has emerged as a major cause of morbidity and mortality in cancer survivors. Effective clinical management of CTRCD is impeded by a lack of sensitive diagnostic and prognostic strategies. Circulating molecular markers could potentially address this need as they are often indicative of cardiac stress before cardiac damage can be detected clinically. A growing understanding of the underlying physiological mechanisms for CTRCD has inspired research efforts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…Further research is warranted to identify sensitive biomarkers for the detection of early cardiovascular disease in childhood cancer survivors. 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is warranted to identify sensitive biomarkers for the detection of early cardiovascular disease in childhood cancer survivors. 11…”
Section: Discussionmentioning
confidence: 99%
“…However, measurements of these markers in the long-term follow up have low diagnostic capabilities. 11 Nonetheless, knowledge is sparse regarding biomarkers other than troponin and N-terminal pro-B-type natriuretic peptide in childhood cancer survivors. 12 Untargeted analysis of a large number of proteins, proteomics, has been put forward both as a mean to identify novel cardiovascular biomarkers in childhood cancer survivors and to unveil novel mechanisms for developing cardiovascular disease.…”
mentioning
confidence: 99%
“…The function of ORMFs implies the pathways of ANTs, especially the immunological infiltration and the angiogenesis signaling pathway, to be critical issues in the ongoing studies of ANTs-induced cardiotoxicity. Immunity contributed significantly to the occurrence and progression of AIC [ 33 ]. Proteins in the blood represent drug-induced immune-mediated reactions and may potentially be sensitive biomarkers of drug-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that elevated cardiac biomarkers such as BNP/NT-proBNP, cardiac troponin are associated with subsequent development of CTRCD or LVDD ( 34 ). Furthermore, in some patients, abnormal cardiac biomarkers appeared earlier than the time when LVEF was below normal ( 35 ). Therefore, regular cardiac biomarker testing can aid in the early detection of cardiotoxicity, such as myocarditis, heart failure, and asymptomatic subclinical cardiac injury.…”
Section: Discussionmentioning
confidence: 99%